PENINGKATAN HASIL BELAJAR IPA MELALUI MEDIA AUDIO VISUAL PADA SISWA KELAS VI DI SDN GUNUNG BUNDER 01 PAMIJAHAN - Muhammad Aldiansyah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This study aims to find out how to improve the quality of learning activities so that they are more effective, so as to be able to improve science learning outcomes for class VI students. Research conducted using the Classroom Action Research approach Suharsimi Arikunto (2017: 19) defines Classroom Action Research as